2007
DOI: 10.1016/j.jcrs.2006.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Microcoaxial phacoemulsification

Abstract: Laboratory results indicate that microcoaxial phacoemulsification through a 2.2 mm incision offers fluidic-, thermal-, and incision-related benefits over sleeveless bimanual microphacoemulsification. Moreover, a full-sized single-piece acrylic IOL could be safely implanted without enlarging the 2.2 mm incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 12 publications
(10 reference statements)
0
21
0
1
Order By: Relevance
“…Recent studies comparing biaxial phacoemulsification and microcoaxial phacoemulsification [18][19][20][21][22] describe both techniques as safe and effective with comparable advantages and disadvantages. It seems that at present, most surgeons prefer microcoaxial phacoemulsification over biaxial phacoemulsification based on their level of experience with the coaxial technique.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies comparing biaxial phacoemulsification and microcoaxial phacoemulsification [18][19][20][21][22] describe both techniques as safe and effective with comparable advantages and disadvantages. It seems that at present, most surgeons prefer microcoaxial phacoemulsification over biaxial phacoemulsification based on their level of experience with the coaxial technique.…”
Section: Discussionmentioning
confidence: 99%
“…In microcoaxial phacoemulsification, irrigation, aspiration, and phacoemulsification are performed with the same instrument (phaco handpiece), used in standard coaxial phacoemulsification. [1][2][3] The only difference between the 2 techniques is the smaller main incision in microcoaxial phacoemulsification, which is the result of the development of the phaco tip sleeves. In biaxial MICS, however, the irrigation and phacoemulsification aspiration steps are separate; an irrigation chopper is used for irrigation and a sleeveless phaco tip for aspiration and phacoemulsification.…”
mentioning
confidence: 99%
“…Generally, bimanual phacoemulsification has the advantage of small incision sites (individually 1.2 mm-1.4 mm in length) in comparison to a relatively large incision (1.8 mm-3.2 mm) in coaxial phacoemulsification (Gajjar et al 2007;). Coaxial phacoemulsification, however, has advantages of a single incision site, better temperature control, easier handling, better sealability, and several fluidic benefits (Osher and Injev 2007). Even though both types of phacoemulsification offer advantages and are still in use, it has been reported that bimanual phacoemulsification has more disadvantages such as limited infusion of the irrigation solution (Osher and Injev 2007), chamber instability caused by leakage at the two incision sites (Gajjar et al 2007;), higher possibility for bacteria to enter through the multiple incisions (Gajjar et al 2007), and regular occurrence of physical wound trauma due to tight angular movement of the instrument through the small incisions ).…”
Section: Introductionmentioning
confidence: 99%